2015
DOI: 10.14257/ijsia.2015.9.7.22
|View full text |Cite
|
Sign up to set email alerts
|

Load Spectrum and Fatigue Life Computer Analysis of Prestressed Concrete Bridges

Abstract: With respect to fatigue damage of heavy traffic on the bridge structure, this paper studied on load spectrum and fatigue simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…The tests on slabs showed that the fatigue life under a moving load is lower than for a load that is repeatedly applied at the same position (Sonoda and Horikawa, 1982). For partially prestressed concrete beams (Harajli and Naaman, 1985;Naaman and Founas, 1991;Shahawi and Batchelor, 1986;Xin et al, 2015;Xin et al, 2017;Zeng et al, 2014), experiments showed that the failure mode could change from flexural failure to shear failure, which led to thorough research on this topic.…”
Section: Fatigue Strength Of Concrete Structuresmentioning
confidence: 99%
“…The tests on slabs showed that the fatigue life under a moving load is lower than for a load that is repeatedly applied at the same position (Sonoda and Horikawa, 1982). For partially prestressed concrete beams (Harajli and Naaman, 1985;Naaman and Founas, 1991;Shahawi and Batchelor, 1986;Xin et al, 2015;Xin et al, 2017;Zeng et al, 2014), experiments showed that the failure mode could change from flexural failure to shear failure, which led to thorough research on this topic.…”
Section: Fatigue Strength Of Concrete Structuresmentioning
confidence: 99%
“…For partially pre-stressed concrete structures, reinforcement stress suddenly increases when the concrete cracks. Therefore, the maximum and minimum load values selected in the fatigue test must make the reinforcement stress repeatedly span sudden increase points of its stress [27]. The details are shown in Table 3.…”
Section: Corrosion Testsmentioning
confidence: 99%
“…The summarized experiments are unique in nature, as the tested specimens give us insight in the behavior of slab-between-girder bridges as a structural system. Most fatigue testing in the past focused on testing small specimens [22,23] or structural elements [24][25][26][27][28][29][30][31] instead of structural systems. The insights from these experiments are now reported for the first time in the context of bridge assessment.…”
Section: Introductionmentioning
confidence: 99%